Beyond unsustainable leadership: critical social theory for sustainable leadership. Issue 4 (4th September 2017) - Bendell, Jem; Sutherland, Neil; Little, Richard
Abstract : Purpose: The purpose of this paper is to prepare the conceptual groundwork for the future study of leadership for sustainable development. The paper demonstrates the relevance of Critical Leadership Studies to future research on sustainable development policies and practices. A critical approach is also applied to concepts of sustainable development, with three paradigms of thought described. Design/methodology/approach: The approach taken is an extensive literature review in fields of leadership and sustainable development, with a focus on some of the broad assumptions and assertions in those literatures. Findings: A key finding is that leadership studies drawing from critical social theory can provide important insights into future research and education on leadership for sustainability. This literature shows that some assumptions about leadership may hinder opportunities for social or organisational change by reducing the analysis of factors in change or reducing the agency of those not deemed to be leading. These limitations are summarised as "seven unsustainabilities" of mainstream leadership research. Research limitations/implications: The paper calls for the emerging field of sustainable leadership to develop an understanding of significant individual action that includes collective, emergent and episodic dimensions. The paper then summarises key aspects of the papers in this special issue on leadership for sustainability. Practical implications: The implications for practice are that efforts to promote organisational contributions to sustainable development should not uncritically draw upon mainstream approaches to leadership or the training of leaders. Originality/value: The authors consider this the first paper to provide a synthesis of insights from Critical Leadership Studies for research in sustainability.